When a ribosomal protein grows up – the ribosome assembly path of Rps3 - Brigitte Pertschy (Microbial Cell)
The biogenesis of ribosomes is a central process in all dividing cells. Eukaryotic ribosomes are composed of a large 60S and a small 40S subunit, each comprising a complex assembly of ribosomal RNA (rRNA) and ribosomal proteins (r-proteins). The synthesis of these constituents is spatially separated, with r-proteins being produced by translation in the cytoplasm, while rRNA is generated by transcription in the nucleus. Hence, the arrangement of r-proteins and rRNA into large ribonucleoprotein complexes requires dedicated mechanisms ensuring their encounter in the same compartment. To this end, r-proteins need to be safely delivered to the nucleus where they assemble with the rRNA. Beyond these initial challenges, the synthesis of ribosomes does not merely comprise the joining of r-proteins with rRNA, but occurs in a complex assembly line involving multiple maturation steps, including the processing and folding of rRNA. R-proteins usually have composite rRNA binding sites, with several different rRNA helices contributing to the full interaction. Not all of these interaction sites may already be accessible at the point when an r-protein is incorporated, necessitating that some of the r-protein-rRNA contacts are formed at later maturation stages. In our two recent studies, we investigated the ribosome assembly path of r-proteins in the yeast Saccharomyces cerevisiae using the small subunit r-protein S3 (Rps3) as a model. Our studies revealed intricate mechanisms to protect the protein, transport it into the nucleus, integrate it into pre-ribosomal precursor particles and promote its final stable association with 40S subunits.